Prevalence of childhood hearing impairment of different severities in urban and rural areas: a nationwide population-based study in Taiwan. Issue 3 (30th March 2018) - Lin, Cheng-Yu; Tseng, Yen-Cheng; Guo, How-Ran; Lai, Der-Chung
Abstract : Objective: Childhood hearing impairment (CHI) is a major developmental disability, but data at the national level are limited, especially those on different severities. We conducted a study to fill this data gap. Design: A nationwide study on the basis of a reporting system. Setting: To provide services to disabled citizens, the Taiwanese government maintains a registry of certified cases. Using data from this registry, we estimated prevalence rates of CHI of different severities from 2004 to 2010 and made comparisons between urban and rural areas. Participants: Taiwanese citizens ≤17 years old. Primary outcome measures: To qualify for CHI disability benefits, a child must have an unaided pure-tone better ear hearing level at 0.5, 1 and 2 kHz with an average ≥55 decibels (dB), confirmed by an otolaryngologist. The severity was classified by pure-tone better ear hearing level as mild (55–69 dB), moderate (70–89 dB) and severe (≥90 dB). Results: The registered cases under 17 years old decreased annually from 4075 in 2004 to 3533 in 2010, but changes in the prevalence rate were small, ranging from 7.62/10 000 in 2004 to 7.91/10 000 in 2006. The prevalence rates of mild CHI increased in all areas over time, but not those of moderate or severe CHI. Rural areas had higher overall prevalence rates than urban areas in all years, with rate ratios (RRs) between 1.01 and 1.09. By severity, rural areas had higher prevalence rates of mild (RRs between 1.08 and 1.25) and moderate (RRs between 1.06 and 1.21) CHI but had lower prevalence rates of severe CHI (RRs between 0.92 and 0.99). Conclusion: While rural areas had higher overall prevalence rates of CHI than urban areas, the RRs decreased with CHI severity. Further studies that identify factors affecting the rural–urban difference might help the prevention of CHI.